Immunohistochemical and morphologic findings in columnar cell lesions of the breast - Ebru Demiralay; Beyhan Demirhan; Alper Koçbiyik; Aylin Sar; Gülüm Altaca (Wolters Kluwer Medknow Publications, 2011)
Background: Columnar cell lesions (CCLs) with or without atypia frequently coexist with invasive or in situ breast carcinomas. In this study, 39 mastectomy specimens containing CCLs coexisting with invasive carcinomas were retrospectively analyzed for cellular characteristics and structural pattern of CCL neighboring the tumor. Materials and Methods: The expression of estrogen receptor (ER), progesterone receptor (PR), and p53 antibodies in CCL and coexisting invasive tumors, type of invasive tumor, histopathologic grade, and presence of atypia in CCL have been studied. Results: Sixteen (41%) of all CCLs were with atypia, whereas 23 (59%) of them were without atypia. No correlations were found between the presence of CCLs with atypia and either the morphologic type of carcinoma or histopathologic grade of the tumors. Presence of atypia in the CCL was not correlated with the expression of p53 in the invasive tumors. CCLs without atypia dominated in Grade III tumors. The percentages of CCLs without atypia were also higher in both ER (−) and PR (−) tumors. Conclusions: CCL with atypia is generally considered to be a precursor of invasive carcinoma; however, in our study, CCLs without atypia more frequently coexisted with breast carcinoma.